Chinese Younger Parents' Quality of Life During the COVID-19 Pandemic: Do Job Changes and Family Conflicts Matter? - Xiaohan Liu; Yashuang Bai; Ning Huang; Farooq Ahmed; Farooq Ahmed; Muhammad Shahid; Jing Guo (Frontiers Media S.A., 2022)
The quality of life (QoL) might have been decreased owing to social disruptions in daily life and basic functioning after the coronavirus disease (COVID-19) pandemic. This work aims to examine the relationship between job changes, family conflicts, and QoL among parents during COVID-19 in China. We recruited 1,209 adults through an online cross-sectional survey in China during the COVID-19 lockdown from April 21 to April 28, 2020. Convenient and cluster sampling methods were used to recruit parents. The global health items in the Patient-Reported Outcomes Measurement Information System (PROMIS) were used as a measurement for QoL. Data were mainly analyzed by multiple linear regression with SPSS. Both marital conflict (β = −0.243, p < 0.001) and parent-child conflict (β = −0.119, p = 0.001) were negatively associated with the QoL among parents during the lockdown. Job changes moderated the relationship between marital conflict and QoL (β = −0.256, p = 0.022). In addition, the interaction effects of job changes and family conflict on QoL were significant only among fathers and one-child families. This study indicated that family conflict was a crucial factor correlated with QoL among young parents in the backdrop of the COVID-19 lockdown. Job changes could interact with marital conflict and parent-child conflict on the quality of life.